An Overview on the Development of Electrochemical Capacitors and Batteries – part II - MARTINS,VITOR L. (2020)
Abstract In the second part of the review on electrochemical energy storage, the devolvement of batteries is explored. First, fundamental aspects of battery operation will be given, then, different materials and chemistry of rechargeable batteries will be explored, including each component of the cell. In negative electrodes, metallic, intercalation and transformation materials will be addressed. Examples are Li or Na metal batteries, graphite and other carbonaceous materials (such as graphene) for intercalation of metal-ions and transition metal oxides and silicon for transformation. In the positive electrode section, materials for intercalation and transformation will be reviewed. The state-of-the-art on intercalation as lithium cobalt oxide and nickel containing oxides will be approached for intercalation materials, whereas sulfur and metal-air will also be explored for transformation. Alongside, the role of electrolyte will be discussed concerning performance and safety, with examples for the next generation devices. Finally, a general future perspective will address both electrochemical capacitors and batteries.